Penerapan Teknologi Tepat Guna Dalam Pembuatan Pupuk Cair Organik dari Limbah Sampah Organik secara Mandiri Skala Rumah Tangga di BTN Bisma Residence Ngabang Kabupaten Landak dalam rangka Memanfaatkan Sampah Rumah Tangga - Tuminah; Balarama, Bertnego; Christiani, Anni; Rego, Gregorius; Yudi; Windi, Albina (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
The waste problem is still a hot issue in several regions in Indonesia, especially in the Landak district of West Kalimantan. Population growth is accelerating and economic growth is indicated by increased production and consumption activities. So what happened at BTN Bisma, located in Ngabang sub-district, Landak district, West Kalimantan, had problems with waste disposal. At BTN Bisma there is only one large trash can in the shape of a truck. Garbage at BTN Bisma is picked up about once a week, so that around the garbage truck bins on a daily basis you can often see garbage piled up outside the tailgate, because the trash can can no longer accommodate garbage, so garbage is scattered outside the trash bin. This sight is certainly very unpleasant, even disgusting because it smells bad. Seeing this fact, our service team has done service at BTN Bisma in the form of making organic liquid fertilizer produced from household waste. The method used in this service is to conduct house-to-house outreach about how to process waste using stacked plastic buckets which can produce organic liquid fertilizer. After being processed for two months, the waste is made into organic liquid fertilizer which is very useful for fertilizing plants, both flower plants around the house and vegetables in the garden.